Production and characterization of biochar from gaharu residue via pyrolysis: article / Saiful Haffizi Roslan, Dr. Jefri Jaapar and Mohibah Musa - Roslan, Saiful Haffizi; Jaapar, Jefri; Musa, Mohibah (2018)
A lab-scale high temperature furnace was utilized to study the effect of residence time (30 min – 150 min) on the yield, chemical and physical properties of biochars issued from the pyrolysis process at 800°C. Afterward, an adsorption capacity analysis was carried out to investigate the amount of Methylene Blue dye adsorbed by the chars. Residence time of 120 minutes was found to be optimal in inducing biochar with improved properties, such as substantial fixed carbon content, enriched functional groups, greater specific surface area and high adsorption capacity. Although the residence time of 150 minutes produced biochar with higher fixed carbon, specific surface area and adsorption capacity, the differences were insignificant. In addition, it was noticed by SEM image that the porous structure of biochar at 150 minutes was blocked by ash content. The pore diameter was also bigger. As a result, biochar at 120 minutes with specific surface area of 152.75 m² g¯¹ and Methylene Blue adsorption capacity of 68.5 mg g¯¹ has promising potential towards wide range of applications.